Afro-descendência: fios do passado que tecem o presente - Fazenda, Sônia Maria Ferreira (2010)
The aim of this Master’s Dissertation is to review the sociological relationship between historical facts relating to black Brazilians throughout history and the way they are portrayed by the literary fiction of Machado de Assis’ and Conceição Evaristo’s work. In it, the social condition of black people and its implications can be seen in demarcated contexts, especially, by the power established through laws like the Lei Áurea that abolished slavery in 1888 and the Act 10639/2003 that obliges African history, literature and culture to be studied in Brazilian schools. We also intend to show that at distinct chronological times, blunt identical problems that, despite appearing under new perspectives, transmit between unequal and effective powers, leaving the black Brazilian in a space yet to be conquered with regard to their full social inclusion.